Durability of high belite cement as new technical solution for concrete - Sara Irico; Sabine Mutke; Federica Bertola; Daniela Gastaldi; Livio Capelli; Fulvio Canonico (Acta Polytechnica CTU Proceedings)
The study presents an investigation on the durability performance of concretes produced with an industrial scale high belite cement. This binder, thanks to the high amount of C-S-H gel and the lower C3S/C2S ratio, is characterized by high durability properties. Good resistance to freeze/thaw cycles, very low chloride migration and excellent resistance to sulfate attack were demonstrated. The accelerated carbonation test revealed that the belite cement, due to the high C2S phase amount, is able to increase its strength over time when exposed to high CO2 concentration. Durability and strength results were compared with those of CEM I, CEM II, and CEM III. In addition, a comparison of the performance of a self-compacting concrete produced with high belite cement and CEM I (as reference) is also presented. The results show that the self-compacting concrete with the high belite cement is able to reach sufficient strengths already after 1 day of hydration, with a low heat development and improved durability properties, compared to CEM I.